A new estimate technology of non-invasive continuous blood pressure measurement based on electrocardiograph. (June 2016) - Wu, Chung-Min; Chuang, Chueh Yu; Chen, Yeou-Jiunn; Chen, Shih-Chung
Various physiological parameters have been widely used in the prevention and detection of diseases. In particular, the occurrence of cardiovascular diseases can be observed through daily measurement of blood pressure. Currently, the most common blood pressure measurement method records blood pressure on the upper arm. This can lead to the subject feeling uncomfortable and tension in the arm from the stress may lead to measurement errors. An electrocardiogram represents the electrical activity during heart function, but also contains blood pressure–related information. This study is an attempt to extract features related to blood pressure from the electrocardiogram signal using a new non-invasive blood pressure measurement technology that utilizes intelligent neural network algorithms to calculate blood pressure values from electrocardiogram parameters. In this study, the average error rate of the blood pressure measurement was lower than 5% compared to the common blood pressure machine. The proposed approach alleviates the errors caused by discomfort, which provides a more feasible method to continuously monitor blood pressure in less stressful conditions. This technology has significant potential for advancing healthcare.